2022
DOI: 10.1186/s12866-022-02728-2
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid biosynthesis is associated with low-temperature adaptation in Rhodosporidium kratochvilovae

Abstract: Background Low temperatures greatly limit the growth of microorganisms. Low-temperature adaptation in microorganisms involves multiple mechanisms. Carotenoids are naturally occurring lipid-soluble pigments that act as antioxidants and protect cells and tissues from the harmful effects of free radicals and singlet oxygen. However, studies on the regulation of carotenoid biosynthesis at low temperatures in microorganisms are limited. In this study, we investigated the correlation between caroteno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
2
2
0
Order By: Relevance
“…It is generally observed that most abiotic stresses cause ROS accumulation in cells. One of our previous studies also confirmed a negative correlation between the increase in carotenoid biosynthesis and ROS accumulation at low temperatures [48]. The lack of a carbon source inevitably induces ROS production [13,26], a phenomenon similar to that encountered in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is generally observed that most abiotic stresses cause ROS accumulation in cells. One of our previous studies also confirmed a negative correlation between the increase in carotenoid biosynthesis and ROS accumulation at low temperatures [48]. The lack of a carbon source inevitably induces ROS production [13,26], a phenomenon similar to that encountered in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Rhodosporidium kratochvilovae YM25235 (isolated from Chenghai Lake, Yunnan, China) is a red yeast that produces polyunsaturated fatty acids (PUFAs) and carotenoids [ 44 , 45 , 46 ]. Our previous research focused on the adaptability of the YM25235 strain to a low temperature [ 47 , 48 ]. However, in industrial applications, the growth of microorganisms is usually limited by nutrient availability [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…The levels of these substances are regulated to normal levels by enzymatic and non-enzymatic antioxidant systems [37]. Notably, β-carotene is the principal non-enzymatic antioxidant found in red yeast cells; in another study, we found a correlation between carotenoid biosynthesis and ROS accumulation in red yeast [38]. In this study, the experimental group (Y79_96SB) exhibited high ROS levels and increased carotenoid synthesis efficiency at 96 h (Figures 2c and 3a).…”
Section: Discussionsupporting
confidence: 50%
“…Carotenoids are lipophilic compounds accumulated in the cell membrane where the variation in chemical structure and thickness of carotenoids may affect the regulations of these compounds [ 54 ]. They present significant biological properties, for example, acting as antioxidants and protecting cells and tissues from the harmful effects of free radicals and singlet oxygen [ 55 ]. In addition, these compounds were reported to engage in photoprotection, and membrane stabilization [ 56 , 57 , 58 ].…”
Section: Significance Of Arthrobacter Spp In the D...mentioning
confidence: 99%